Stem Cell Biomarkers in Chronic Myeloid Leukemia. Issue 4 (2008) - Jiang, Xiaoyan; Zhao, Yun; Forrest, Donna; Smith, Clayton; Eaves, Allen; Eaves, Connie
Abstract : Chronic myeloid leukemia (CML) is a clonal multi-step myeloproliferative disease that is initially produced and ultimately sustained by a rare subpopulation of BCR-ABL + cells with multi-lineage stem cell properties. These BCR-ABL + CML stem cells are phenotypically similar to normal hematopoietic stem cells which are also maintained throughout the course of the disease at varying levels in different patients. Defining the unique properties of the leukemic stem cells that produce the chronic phase of CML has therefore had to rely heavily on access to samples from rare patients in which the stem cell compartment is dominated by leukemic elements. Here we review past and ongoing approaches using such samples to identify biologically and clinically relevant biomarkers of BCR-ABL + stem cells that explain their unusual biology and that may help to design, or at least predict, improved treatment responses in CML patients. These studies are of particular interest in light of recent evidence that chronic phase CML stem cells are not only innately resistant to imatinib mesylate and other drugs that target the BCR-ABL oncoprotein, but are also genetically unstable.